ChemInform Abstract: Copper‐Catalyzed Trifluoromethylation of Aliphatic N‐Arylhydrazones: A Concise Synthetic Entry to 2‐Trifluoromethylindoles from Simple Aldehydes. Issue 6 (21st January 2016) - Prieto, Alexis; Landart, Melissa; Baudoin, Olivier; Monteiro, Nuno; Bouyssi, Didier
Abstract: The trifluoromethylation employing Togni reagent proceeds efficiently for aliphatic aldehyde‐derived substrates bearing the N, N‐diphenylamino group (Ami) as the terminal hydrazone amino group.